The surface geometry of carbonmonoxide and hydrogen co-adsorbed on Ni1 1 1 - Braun, Wolfgang; Steinrück, Hans-Peter; Held, Georg (Surface Science, 2005)
A combination of photoelectron spectroscopy, temperature programmed desorption and low energy electron diffraction structure determinations have been applied to study the p(2 × 2) structures of pure hydrogen and co-adsorbed hydrogen and CO on Ni1 1 1. In agreement with earlier work atomic hydrogen is found to adsorb on fcc and hcp sites in the pure layer with H-Ni bond lengths of 1.74 Å. The substrate interlayer distances, d = 2.05 Å and d = 2.06 Å, are expanded with respect to clean Ni1 1 1 with buckling of 0.04 Å in the first layer. In the co-adsorbed phase CO occupies hcp sites and only the hydrogen atoms on fcc sites remain on the surface. d is even further expanded to 2.08 Å with buckling in the first and second layer of 0.06 and 0.02 Å, respectively. The C-O, C-Ni, and H-Ni bond lengths are within the range of values also found for the pure adsorbates. © 2004 Elsevier B.V. All rights reserved.